Employer Branding and its Impact on Retention of Healthcare Staff-A Study of Nurses in NABH Hospitals in Northern India - Goyal, Ridhya (My University, 2024)
In the complex world of healthcare, nurses are essential in providing quality care to patients and ensuring hospitals run smoothly. However, the retention of nursing professionals is a critical issue in the healthcare sector, particularly in India. Population growth, aging of the population, and changing healthcare needs are all contributing to an ongoing rise in the requirement for healthcare services. Hospitals and healthcare organizations are working hard to recruit and keep a qualified nursing workforce to meet this demand. With a focus on a study carried out under the framework of NABH (National Accreditation Board for Hospitals) accredited private hospitals in Northern India, this thesis explores the critical interface between employer branding and nurse retention with the mediation of organizational culture, employee engagement, and career development. Retaining skilled nursing staff is a significant challenge for the healthcare sector in the northern region. This emphasizes thesignificance of employer branding and how it can influence nurse retention. Thus, this study aims to find out what influence the employer branding tactics of private hospitals with NABH accreditation have on nurse retention rates. In order to determine the relationship between employer branding initiatives and nurse retention, the study takes a multifaceted approach that combines an in-depth literature review, data collection using interviews and surveys, and statistical analysis. A sample of 628 nurse respondents with varying designations from various departments of private hospitals in northern India was included to test the hypothesis using a structured questionnaire. The effects were examined using structural equations through Partial Least Square Structural Equation Modelling. In addition, the study aims to compare different employer branding strategies that bring forth three strategies in terms of social, economic, and developmental aspects. The results demonstrated that, when employee engagement, organizational culture, and career development were taken into account as mediators, there was a complementary mediation relationship and a positive impact of employer branding on retention. This research aims to identify the impact of employer branding and its strategies that contribute to the retention of nurses working in these accredited private hospitals by investigating the perceptions and experiences of the nurses there using a sound theoretical base of social identity and self-determination theory. The theoreticalfoundations of employer vi branding, its applicability in the healthcare industry, and the distinctive dynamics of nurse retention in NABH-accredited private hospitals are some of the major topics covered in this thesis. The findings are anticipated to provide healthcare administrators, human resources professionals, and policymakers with practical insights that will help them develop strategies to improve employer branding and ultimately reduce nursing workforce turnover. This study adds to our understanding of employer branding and nurse retention while providing healthcare organizations with valuable guidance on how to improve retention of their healthcare workforce. It also adds to the larger discussion on health care management and employee retention tactics in the area by addressing this important issue in the context of NABH private hospitals in North India. Finally, it integrates empirical results with theoretical contributions and managerial implications.
Keywords: Employer Branding; Nurse Retention; Organizational Culture; Career Development; Employee Engagement